The Impact of Innovation-oriented Organizational Climate on Employee’s Creative Behavior: A Case Study in Poland - ALQAHTANI, KHALED (The Arab Journal of Administration, 2025)
Innovation serves as a crucial strategy for enterprises navigating complex and dynamic environment. Despite the acknowledged significance of this, the influence of an organization's innovation environment on employees' innovative behavior remains underexplored. In addition, the existing scholarly works have frequently overlooked to examine the specific dimensions of organizational innovation climate and their distinct effects on employee innovation. This study aims to address these gaps by investigating and examining the impact of an innovation-oriented organizational climate on employees' creative behavior. Questionnaires were used to collect data from 32 companies that operate in various fields in Poland. The research findings clearly indicate that three key dimensions (self-directed workability, team cooperation, and organizational incentives) of an innovation-focused organizational climate positively and significantly affect employee innovation behavior. To effectively enhance organizational performance and achieve superior outcomes, business leaders are advised to prioritize creating a supportive and innovation-driven work climate, while concurrently considering the motivational perspectives of the employees.